Cantwell, Theresa Squires. Black and white photograph of three men and three women from Theresa Squires Cantwell's personal photograph collection. - Barrett, Terra
Left to right: William Squires, Theresa (Tess) Murphy (Squires), Peter Thorpe (Peter is Will and Mell's first cousin), Eileen Druken (Squires), Lyle Squires (friend), Jack Murphy, Amelia "Mell" Murphy (Squires).